Analysis Of Fire Countermeasures System In Technical Implementation Unit Of Type A Fire Fighting Dumai City In 2023: Analisis Sistem Penanggulangan Kebakaran Di Upt Pemadam Kebakaran Tipe A Kota Dumai Tahun 2023 - Fitria Rahmadany; Welly Sando (Badnur Medisa Group, 2023)
Fire is an incident that results in loss of life or property and can occur anywhere, for this reason a fire suppression system is needed which is an effort to prevent fires from occurring. The purpose of this study was to find out the fire prevention system in the technical implementation unit for type A firefighters in Dumai City in 2023. This study used a descriptive research methodology with a qualitative approach conducted at the Dumai City Fire Department UPT from May to June 2023. The key informant was the head of sub fire department administration section, the main informant is the head of the fire department technical implementation unit, supporting informants consist of 3 firefighters. Data collection techniques using interviews and observation. Processing data using data triangulation method. The results of the study found that the human resources in the Dumai City fire fighting technical implementation unit were inadequate, as well as the fire fighting facilities and infrastructure were incomplete, standard operating procedures in the fire fighting technical implementation unit existed but were not attached, the extinguishing system was carried out by the technical implementing unit the Dumai City fire department has not been maximized, and the rescue system carried out by the fire department's technical implementation unit has also not been maximized. It is suggested to the Dumai City type A fire fighting technical implementation unit to recruit human resources based on the Regulation of the Minister of Home Affairs No.16/PTR/M/2009 and the procurement of new facilities and infrastructure is expected to be guided by the Regulation of the Minister of Home Affairs No.122/PTR /M/ 2018.